Race and Legislative Responsiveness in City Council Meetings. Issue 6 (November 2019) - Hoang, Bai Linh
Legislative responsiveness under description representation, even at the local level, is often conceptualized as how elites act on or comply with the requests or preferences of minority constituents. In this article, I look at and evaluate a neglected but important dimension of responsiveness. Specifically, I investigate the impact of race on the verbal responses that legislators provide to constituents who speak at local public meetings. Through an analysis of data collected from city council minutes and direct observations of council meetings, I find a lack of evidence for the independent effect of race on legislative responsiveness in these meetings. However, I do find that the impact of race is conditional on the statements expressed by constituents.